Enhancement of therapeutic effect in breast cancer with a steroid-conjugated ruthenium complex. (4th February 2019) - Lv, Gaochao; Qiu, Ling; Li, Ke; Liu, Qingzhu; Li, Xi; Peng, Ying; Wang, Shijie; Lin, Jianguo
Abstract : A hybrid metallic prodrug for targeting PR-positive breast cancer therapy was prepared, which revealed significantly in vivo antitumor effect. Abstract : A new hybrid metallic prodrug Te–S–S–NHC–Ru (Te–S–S–NHC: 17-α-[1, 3-bis(4-( tert -butyl)benzyl)-4-methyl-2, 3-dihydro-1 H -imidazole-bis(2-diethylcarbonate)disulfide-1 H -1, 2, 3-triazol-1-yl]-19-testosterone) was designed and synthesized by a targeting group-drug conjugate strategy with 17α-ethynyl testosterone as the carrier vector to conjugate to our previously reported ruthenium N-heterocyclic carbene complex (NHC–Ru) with a disulfide linkage. It could be applied as a GSH-induced therapeutics system with high selectivity over potential interference by various biological compounds. The anticancer activity of the new ruthenium complex was investigated in vitro and in vivo . MTT assay against progesterone receptor positive MCF-7 (PR+) and progesterone receptor negative MBA-MD-231 (PR−) human breast cancer cell lines revealed that the cytotoxicity of the PR-targeted agent was significantly higher in PR(+) than in PR(−) cells caused by the selective cellular uptake. Moreover, in vivo antitumor activity studies indicated that Te–S–S–NHC–Ru induced a smaller tumor volume and a longer survival time of tumor-bearing mice after treatment. Thus Te–S–S–NHC–Ru may be a promising ruthenium-based anti-cancer agent for the effective treatment of tumors.